Electroacupuncture at Zusanli (ST36), Guanyuan (CV4), and Qihai (CV6) Acupoints Regulates Immune Function in Patients with Sepsis via the PD-1 Pathway. - Yang, Guang; Zheng, BoJun; Yu, Yi; Huang, Jing; Zhu, HongFa; Deng, DingWei; Li, Jian (BioMed Research International, 2022)
Objective. The present study is aimed at investigating the biochemical and clinical effects of electroacupuncture in patients with sepsis. Methods. Patients with sepsis treated at Guangdong Provincial Hospital of Chinese Medicine from July 2019 to December 2020 were included. Patients were randomly assigned to treatment with routine Western medicine (WM group) or treatment with Western medicine plus electroacupuncture based on Western medicine (EA group). Indices associated with immune function and clinical efficacy were determined before and at 3 and 5 days after treatment. Indicators of immune function included the percentage of T lymphocyte subsets, natural killer (NK) cells, and soluble programmed death protein 1 (sPD-1) levels. Indicators of clinical efficacy included infection-related indicators in whole blood; levels of tumor necrosis factor-α (TNF-α), C-reactive protein (CRP), and interferon-γ (INF-γ); and assessments using acute physiology and chronic health evaluation-II (APACHE-II) and sequential organ failure assessment (SOFA) scores. Results. Baseline data were not different between WM (N = 30) and EA groups (N = 30). At day 5 following treatment, the level of sPD-1 in the EA group was lower than that in the WM group. Proportions of CD3 + T lymphocytes, CD4 + T lymphocytes, and NK cells, the percentage of lymphocytes, and INF-γ levels in the EA group were significantly higher than those in the WM group. Compared with the WM group, the white blood cell count (WBC), percentage and count of neutrophils, ratio of neutrophils to lymphocytes, and levels of CRP and TNF-α were significantly decreased in the EA group 5 days after treatment. The APACHE-II score of the EA group was significantly lower than that of the WM group 5 days after treatment. Conclusion. Electroacupuncture may regulate the immune function of patients with sepsis through the PD-1 pathway to achieve an anti-inflammatory state and improve clinical symptoms.